Exploration Characteristics of Trichomes Shading Plant at Melati Bungur Park Malang City - Eko Cahyono; Iin Hindun; Abdulkadir Rahardjanto; Endrik Nurrohman (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Trichomes are structures that cover the surface of plants with hair-like structures and are found in a large number of plants with either unicellular or multicellular forms. Trichomes are one of the important elements in plants, because their presence can be used to identify species based on their appearance, size, type, and content of compounds in them and protect the environment from various kinds of pollutants. Road shade plants are plants planted on the side of the road that function in absorbing pollutants. The purpose of the study was to explore the type, shape, size of trichomes of road shade plants in Malang City. Qualitative descriptive research method. The research was conducted at the Biology Laboratory of the University of Muhammadiyah Malang. The study was conducted in July 2021 using a sample of 4 species of leaf organ plants for the road shade Melati Bungur park Malang City. The results showed that Bauhinia purpurea L found non-glandular trichomes, simple unicellular shape, 159µm long and 13.7µm diameter. Erythrina crista-galli L, a type of non-glandular trichome, simple unicellular form, 240µm long, and 26.9µm in diameter. Tabebuia aurea (Manso) Benth type of non-glandular trichomes, scales, diameter 76.9µm. Two types of trichomes were found in Muntingia calabura L, non-glandular with a star shape, 163µm long, and 5.7µm in diameter. The capitate glandular trichomes are 22µm long and 108µm in diameter, while the peltate trichomes are 15.4µm in diameter.